Clinical applications of exosome membrane proteins. Issue 1 (24th February 2020) - Hu, Qian; Su, Hang; Li, Juan; Lyon, Christopher; Tang, Wenfu; Wan, Meihua; Hu, Tony Ye
Abstract: Extracellular vesicles (EVs) are small membranous particles that can mediate cell-to-cell communication and which are divided into at least three categories according to their subcellular origin and size: exosomes, microvesicles, and apoptotic bodies. Exosomes are the smallest (30–150 nm) of these EVs, and play an important role in EV-mediated cell-to-cell interactions, by transferring proteins, nucleic acids and, lipids from their parental cells to adjacent or distant cells to alter their phenotypes. Most exosome studies in the past two decades have focused on their nucleic acid composition and their transfer of mRNAs and microRNAs to neighboring cells. However, exosomes also carry specific membrane proteins that can identify the physiological and pathological states of their parental cells or indicate their preferential target cells or tissues. Exosome membrane protein expression can also be directly employed or modified to allow exosomes to serve as drug delivery systems and therapeutic platforms, including in targeted therapy approaches. This review will briefly summarize information on exosome membrane proteins components and their role in exosome–cell interactions, including proteins associated with specific cell-interactions and diseases, and the potential for using exosome membrane proteins in therapeutic targeting approaches.